Functional Dissection of C. elegans bZip-Protein CEBP-1 Reveals Novel Structural Motifs Required for Axon Regeneration and Nuclear Import - Malinow, Rose Aria; Ying, Phoenix; Koorman, Thijs; Boxem, Mike; Jin, Yishi; Kim, Kyung Won (Frontiers in Cellular Neuroscience, 2019)
The basic leucine-zipper (bZIP) domain transcription factors CCAAT/enhancer-binding proteins (C/EBP) have a variety of roles in cell proliferation, differentiation, and stress response. In the nervous system, several isoforms of C/EBP function in learning and memory, neuronal plasticity, neuroinflammation and axon regeneration. We previously reported that the C. elegans C/EBP homolog, CEBP-1, is essential for axon regeneration. CEBP-1 consists of 319 amino acids, with its bZIP domain at the C-terminus and a long N-terminal fragment with no known protein motifs. Here, using forward genetic screening with targeted genome editing, we have identified a unique domain in the N-terminus that is critical for its in vivo function. Additionally, we characterized three nuclear localization signals (NLS) in CEBP-1 that act together to mediate CEBP-1’s nuclear import. Moreover, the Importin-α, IMA-3, can bind to CEBP-1 via one of the NLS. ima-3 is ubiquitously expressed in all somatic cells, and ima-3 null mutants are larval lethal. Using Cre-lox dependent neuron-specific deletion strategy, we show that ima-3 is not critical for axon development, but is required for axon regeneration in adults. Together, these data advance our understanding of CEBP-1’s function, and suggest new regulators that remain to be identified to expand the CEBP-1 protein interactome.